TANTANGAN YANG DIHADAPI MAHASISWA DALAM MENERAPKAN SELF-REGULATED LEARNING SELAMA PEMBELAJARAN DARING - Presly Emilya Ninu Tnunay; Kesya Yuliana Pandie; Olimpia Mau Weni; Defyta Demaris E. Kelen; Ventriani Taosu; Indriani Maria (JIP: Jurnal Ilmu Pendidikan, 2025)
Online learning offers flexibility, but presents challenges in implementing Self-Regulated Learning (SRL). This study aims to identify and analyze these challenges through a comprehensive literature review of 4 relevant journals (2023-2025), using thematic analysis. The results showed four main themes: cognitive challenges (difficulty managing information), metacognitive (difficulty monitoring understanding), affective (motivational and stress issues), and environmental (access to technology and platform quality). These findings are consistent with Zimmerman’s (2000) SRL theory, which emphasizes the integration of cognition, metacognition, and motivation. These challenges are interrelated, forming a negative cycle that hinders learning success. This study highlights the need for online learning strategies that are more supportive and responsive to students’ needs in managing information, monitoring understanding, regulating motivation, and accessing adequate technology and support.